Adding immersive virtual reality to a science lab simulation causes more presence but less learning. (April 2019) - Makransky, Guido; Terkildsen, Thomas S.; Mayer, Richard E.
Abstract: Virtual reality (VR) is predicted to create a paradigm shift in education and training, but there is little empirical evidence of its educational value. The main objectives of this study were to determine the consequences of adding immersive VR to virtual learning simulations, and to investigate whether the principles of multimedia learning generalize to immersive VR. Furthermore, electroencephalogram (EEG) was used to obtain a direct measure of cognitive processing during learning. A sample of 52 university students participated in a 2 × 2 experimental cross-panel design wherein students learned from a science simulation via a desktop display (PC) or a head-mounted display (VR); and the simulations contained on-screen text or on-screen text with narration. Across both text versions, students reported being more present in the VR condition ( d = 1.30); but they learned less ( d = 0.80), and had significantly higher cognitive load based on the EEG measure ( d = 0.59). In spite of its motivating properties (as reflected in presence ratings), learning science in VR may overload and distract the learner (as reflected in EEG measures of cognitive load), resulting in less opportunity to build learning outcomes (as reflected in poorer learning outcome test performance). Highlights: The consequences of adding immersive virtual reality to a simulation was examined. The impact of the level of immersion on the redundancy principle was investigated. EEG was used to obtain a direct measure of cognitive processing during learning. Students reported higher presence but learned less in the immersive VR condition. Students also had higher cognitive load based on EEG in the immersive VR condition.